Manajemen Mutu Terpadu Lembaga Pendidikan Pondok Pesantren - Mega Sobri Putri; Titik Umiati; M. Syahran Jailani; Harlina Harja; Yennizar Yennizar; Amrizal Amrizal (Departement of Mathematics Education, 2024)
Islamic boarding schools are non-formal educational institutions inherited from their ancestors and have made a big contribution in creating quality human resources. Nowadays Islamic boarding schools have modernized education as a form of effort to improve the quality of Islamic boarding schools in meeting community demands. Improving the quality of Islamic boarding schools must be carried out continuously and the concept of Integrated Quality Management (MMT) or Total Quality Management (TQM) can be a reference in quality-based management of Islamic boarding schools, because Total Quality Management (TQM) is an approach or management to improve quality overall. comprehensive, competitive, effectiveness and flexibility of the entire organization and oriented towards customer satisfaction.